A COMPARATIVE STUDY ON DRUG USE OF ANTIMICROBIAL AGENTS IN MEDICAL AND SURGICAL INTENSIVE CARE UNITS OF A TERTIARY CARE HOSPITAL. - Paul, Nimin; V, Santhosh Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: To identify the pattern of drug utilization of antimicrobials in prescriptions of patients admitted at medical intensive care unit (MICU) and surgical intensive care unit (SICU) department and to analyze the utilization of different classes of drugs. Methods: A prospective observational study was carried out in 10 bedded medical and surgical intensive care unit (ICU) of tertiary care hospital, Adayar, from October 1st 2016 to March 1st 2016. The study was performed in 100 prescriptions. The relevant data on drug prescription of each patient were collected from in-patient records. The demographic data, disease data, and the utilization of different classes of antimicrobial agents (AMAs) were analyzed. Results: In MICU, a total of 648 drugs were prescribed during the period of stay and AMAs accounted for 15% of total drug. The average length of stay was found to be 8 (±8.73). The mean number of drugs received by patients is 11.6 ± 2 drugs. The most frequently prescribed AMAs were ceftriaxone followed by meropenem and clindamycin. Cephalosporin is commonly prescribed due to their relatively lower toxicity and broader spectrum activity. The generally prescribed AMA combination was amoxicillin + clavulanic acid (32.50%) and piperacillin + tazobactam (27.50%). The laboratory reported positive cultures for 30 patients. The most prevailing organisms were Escherichia coli (50%). In SICU, a total of 780 drugs were prescribed during the period of stay and AMAs accounted for 18% of total drug. An average of 5 (±2.0) drugs was prescribed for each patient and each prescription contains an average of 2 (±0.9) AMAs. The results indicated that ceftriaxone was the most commonly prescribed AMAs (22%), followed by meropenem (18%), ciprofloxacin (18%), and colistin (8%). A total of five AMA combination therapies were used in SICU. Among them, piperacillin+clavulanic acid (36.84%) was the most commonly prescribed combination. In the study, 30 (60 %) cases had microbial growth and have performed sensitivity test. Conclusion: A wide class and percentage of AMAs were prescribed in ICUs. There is a need of antimicrobial agent's usage guidelines and restriction policies for the rational prescribing of antimicrobials in critically ill patients.